AN ANALYSIS OF HIGHER ORDER THINKING SKILL (HOTS) IN MERDEKA CURRICULUM ENGLISH TEXTBOOK â€œPATHWAY TO ENGLISHâ€ PUBLISHED BY ERLANGGA FOR GRADE X OF SENIOR HIGH SCHOOL - Arisman, Arisman; Maisarah, Ira; Yunita, Wisma; Sujarwati, Iis; Sofyan, Dedi (Jurnal Bilingual, 2024)
Higher order thinking skills (HOTS) refer to the more advanced mental processes outlined in Anderson and Krathwohl's updated version of Bloom's taxonomy (2021), comprising analysis, evaluation, and creation.". This research aimed to investigate the composition of HOTS (Higher Order Thinking Skill) in language tasks and knowledge of the English textbook on titled â€œPathwayâ€ To English For SMA/MA Grade X and to explain the dominant cognitive dimension used in this textbook. The design of this research was descriptive qualitative. This research is classified as a content analysis. A table checklist based on the cognitive domain of the revised Bloomâ€™s taxonomy was the instrument of this research. The findings of the research indicate that for language skills, this book is more concerned with HOT than LOTS with the percentage of HOTS at 58,34% and LOTS at 41,66%.Â  The result showed The most dominant level of thinking skill of language skill in this book is analyze (C4), followed by apply (C3), remember (C1), create (C6), evaluate (C5), and understand (C2).Â  For knowledge, it can be concluded that the composition of the Higher Order Thinking Skill (HOTS) presented in the instruction question on the English Textbook is not lower than the Lower Order Thinking Skill (LOTS) with the percentage of HOTS at 20,83% and LOTS at 79,17%. The dominant composition is Apply (C3), followed by Remember (C1), Apply (C4), and Understand (C2). Â Â The researcher concludes that for language skill and knowledge, the cognitive dimension of each instruction question is present in the imbalance portion. Based on the result, this book has followed the ministry of education regulation and mereka curriculum in providing HOTS material in the teaching and learning process for language skills and proving LOTS material for knowledge because grammar and vocabulary teach the basics of language. It is suggested for teachers who use this book to be innovative, and creative, even teachers can adapt from other sources in giving instruction to develop studentsâ€™ critical thinking.